Antenna 5.8 GHz dengan Output Perbedaan Fasa 90 Derajat Ganda Menggunakan Jaringan Matriks Butler Feeding - Mujahidin, Irfan; Prasetya, Dwi Arman; Arifuddin, Rahman; Arinda, Putri Surya (Program Studi Teknik Elektro Universitas Khairun, 2021)
A complex design of electromagnetic feeding network circuit components is needed for a wireless communication network system, and expensive materials, especially for electromagnetic components at a high frequency of 5.8 GHz with dual 90-degree phase difference output using butler matrix Feeding Network for wireless communication network systems. It is novel in form and has a frequency-free, frequency-free, non-complex configuration of microstrip electromagnetic circuits, and uses inexpensive materials at a frequency of 5.8 GHz. This system is a package consisting of a 5.8 GHz microstrip antenna with a rectangular microstrip antenna array and a Butler matrix of four inputs and outputs to achieve a double 90-degree phase difference. The antenna uses a via hole for the transmission line to the network feeding system, has one band and shallow bandwidth with four ports, and has one working frequency, namely 5.58 GHz under the S criterion -10dB, and uses a via hole for the transmission line to the network feeding system, the radiation pattern is forward, the gain level is 6.83dB, and the feeding impedance is 50 Ohm. S11 -26.19 dB for the 90-degree hybrid coupler, S21 31.65 dB, S51 -26.18 dB, and S61 32.52 dB which means these are all working well, and the overall size of this structure is 80mm x 65mm with FR4 of 4.4 dielectric constant having 50 ohms.